2021
DOI: 10.1155/2021/5596110
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Early Postnatal-Care Service Utilization and Its Associated Factors among Mothers in Hawassa Zuria District, Sidama Regional State, Ethiopia: A Cross-Sectional Study

Abstract: Background. A postnatal care given after childbirth is a critical care to promote health and to prevent complications of the mother and newborn. However, utilization of this service is low in Ethiopia, and little is known about its coverage and determinants. Thus, this study aimed to assess the prevalence of early postnatal-care service utilization and its associated factors among mothers in Hawassa Zuria district, Sidama Regional State, Ethiopia. Methods. A cross-sectional study was conducted from 20 February… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
3
13
2
Order By: Relevance
“…The minimum sample size required for the study was determined by using a single population proportion formula true0n=(Zα/2)2p(1p)d2 with assumptions of 95% CI, 0.05 margin of error and established prevalence (p=23.7%) of EPNC service usage and its associated factors among mothers in Hawassa Zuria district, Sidama regional state, Ethiopia,9 with adding a 10% non-response rate. Based on the above assumption consideration the final sample size became (n=306).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum sample size required for the study was determined by using a single population proportion formula true0n=(Zα/2)2p(1p)d2 with assumptions of 95% CI, 0.05 margin of error and established prevalence (p=23.7%) of EPNC service usage and its associated factors among mothers in Hawassa Zuria district, Sidama regional state, Ethiopia,9 with adding a 10% non-response rate. Based on the above assumption consideration the final sample size became (n=306).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Uganda, 7 and South Sudan, 8 reported 15.4% and 11.4%, respectively. It also noted variations in research conducted in Ethiopia, like Southern Ethiopia at Hawassa Zuria, 9 and Wonago district, 10 North Ethiopia, 11 reported 29.7%,13.7% and 34.3%, respectively.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have been conducted to investigate the utilization of PNC, as well as the factors that influence it. Several studies have linked it to maternal-related influencing factors such as age of women ( Yoseph et al, 2021 ), educational level of the women ( Ahinkorah et al, 2021 ), occupational status of women and husbands ( Ahinkorah et al, 2021 ), wealth index ( Ahinkorah et al, 2021 ), antenatal care (ANC) ( Belachew et al, 2016 ), media exposure ( Ahinkorah et al, 2021 ), place of delivery ( Belachew et al, 2016 ; Limenih et al., 2016 ; Somefun & Ibisomi, 2016 ), wealth index ( Mekonnen et al, 2021 ; Somefun & Ibisomi, 2016 ). In addition, the utilization of PNC can be affected by other factors, such as time taken to get the nearest health facility ( Ndugga et al, 2020 ), planned and wanted pregnancy ( Yoseph et al, 2021 ), health profession preferred by women, source of information about maternal care, duty service of maternal health care ( Ahinkorah et al, 2021 ), number of living children ( Debie & Tesema, 2021 ), cultural practices ( Belachew et al, 2016 ; Miller et al, 2016 ), lack of counselling, transportation problem, distance from the health institutions ( Hordofa et al, 2015 ; Mukonka et al, 2018 ; Somefun & Ibisomi, 2016 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Factors such as education and availability of economic resources as facilitators are consistent with previous findings in Africa that showed that women that were employed and had received a secondary school level education were more likely to attend PNC services [ 21 , 27 , 33 – 36 ]. Additionally, we argue that women who are knowledgeable and educated would recognize attendance at a PNC as their primary role and responsibility [ 23 , 34 – 36 , 48 ]. Furthermore, our study highlighted that seeking treatment for an illness facilitates attendance at PNC and it builds upon findings that assert that knowledge of an infant’s danger signals also motivates a woman to attend PNC services with her baby [ 22 , 47 ].…”
Section: Discussionmentioning
confidence: 99%